ANALISIS GAYA BELAJAR VISUAL DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH SISTEM PERSAMAAN LINEAR DUA VARIABEL - Aribah Errina; Mohamad Rif'at; Silvia Sayu (Jurnal AlphaEuclidEdu, 2021)
This review means to depict the investigation of visual learning styles as far as critical thinking capacity of understudies' two-variable direct condition framework at MTS Negeri 3 Mempawah. The examination strategy utilized is enlightening subjective as contextual analyses. The subjects in this study were class VIII students at MTS Negeri 3 Mempawah. The number of students who were used as research subjects were 38 students who had studied the material for a two-variable system of linear equations. In this study, six students were selected consisting of two students who had SPLDV Problem Solving Ability in terms of high, medium, low learning styles. The object of this exploration is Visual Learning Style as far as Critical thinking Capacity. In light of the aftereffects of information examination, meetings and conversation, it can be concluded that Analysis of Visual Learning Styles Judging from the SPLDV Problem-Solving Ability of MT.S Negeri 3 Mempawah Students" shows that students' problem-solving abilities are relatively balanced with learning styles. As a rule, understudies who have high numerical critical thinking capacities have great visual learning styles, understudies with moderate critical thinking capacities have great visual learning styles, understudies with low numerical critical thinking capacities have great visual learning styles.